Gambaran Tingkat Risiko Jatuh pada Lansia Berdasarkan Berg Balance Scale di Puskesmas Muara Dua Kota Lhokseumawe 2023 - Salsabila, Salsabila; Nadira, Cut Sidrah; Maulina, Nora (Jurnal Ilmiah Manusia Dan Kesehatan, 2026)
The elderly are an age group of humans who have entered the final stages of their life. As we age, the human body will experience morphological changes in the body, muscles, bones and joints. Deterioration and morphological changes in muscles occur, causing functional changes in muscles, namely a decrease in strength, muscle contraction, muscle elasticity and flexibility, this causes the risk of falls in the elderly to tend to increase. Fall risk is a situation where a person has the potential to experience an increased chance of falling. The purpose of this research is as a screening effort to determine the level of risk of falls in the elderly in the Muara Dua Health Center working area, Lhokseumawe City. This research is descriptive observational with a cross sectional approach with a total of 76 respondents. This research was carried out at the Muara Dua Community Health Center, Lhokseumawe City. The sample in this study was elderly people who met the inclusion and exclusion criteria. The sampling technique in this research was purposive sampling. The results of the study showed that elderly people in the Muara Dua Community Health Center working area, Lhokseumawe City, had a low fall risk level of 96.1% (73 people), a medium fall risk level of 3.9% (3 people) and a high fall risk level was not found. The conclusion obtained in this study was that of the 76 respondents, the majority had a low fall risk level of 96.1% (73 people).